DISLOCATING FRICTION MODEL OF MANY LAYERED COATINGS - Artemchuk, V. V. (Science and Transport Progress, 2007)
For maintenance of the existing rolling-stock in working order it is necessary to carry out qualitative repair. One of directions of development of repair manufacture is the development of new technologies of restoration of the worn out details. It is considered disposition model of friction and influence of lamination on wear resistance of coverings.